Answer:
52.49 Kg
Explanation:
Let m1 and v1 denote your mass and velocity respectively
Let m2 and v2 denote your friends mass and velocity respectively
Kinetic energy is given by
[tex]KE= 0.5mv^{2}[/tex]
Since your kinetic energies are the same hence
[tex]0.5m1(v1)^{2}=0.5m2(v2)^{2}[/tex]
[tex]m1(v1)^{2}=m2(v2)^{2}[/tex] and making m2 the subject then
[tex]m2=\frac { m1(v1)^{2}}{(v2)^{2}}[/tex]
Since v2 is v1+0.28v1=1.28v1
Substituting m1 for 86 Kg
[tex]m2=\frac { 86 Kg(v1)^{2}}{(1.28v1)^{2}}= 52.49023\approx 52.49 Kg[/tex]